PEMBUATAN VIDEO COMPANY PROFILE SEBAGAI SARANA INFORMASI TIAP BIDANG YANG ADA PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA BENGKULU - irul, Khairullah irul; Tamara Cindy Samsita Rani; Serlina Adelia; Fekri Pratama; Heru Susanto (Lembaga Penelitian Pengabdian Masyarakat Penerbitan dan Percetakan Indonesian Scholar Khiar Wafi (LPPMPP IKHAFI), 2024)
In an agency, company profile video is an important part. To facilitate information about the services provided to the wider community which is considered very effective in the era of increasing technological advances, various forms of communication media are needed that can target everyone with interesting and interactive information and promotions. One of them is the existence of a company profile video that contains educational videos to the public to obtain information about various services provided by the Bengkulu City Education and Culture Office. There are four fields that need to be introduced to the community, namely the Field of Energy Development, the Field of Basic Education Development, the Field of Early Childhood Education, and the Field of Culture. This video profile is made to provide a brief overview that can represent and form the image of an agency. Company profile videos are important because they can convey information more effectively. Company profile videos can convey a full message in a short time by combining text, sound, and images. An agency can also more easily convey messages to the community at large. The method used in making this video profile is the Multimedia Development Life Cycle (MDLC) model. MDLC includes the stages of concept, design, material collecting, assembly, testing and distribution. The creation of this video profile is expected to provide benefits for viewers and the public who have an interest in the Education and Culture Office of Bengkulu City.